Perdas e valor nutritivo de silagens de Brachiaria aditivadas com casca de soja - Dantas, Carlos Clayton Oliveira (2012)
With the aim to evaluate the losses for gases and effluents, the recovery of nutrients, the chemical and bromatological composition, to estimate the fractions of protein and carbohydrates, as well as in situ ruminal degradability of Brachiaria decumbens silage with soybean hulls, an experiment was conducted to compare five inclusion levels of soybean hulls: 0, 10, 20, 30 and 40% of 3 natural matter, with five replicates per treatment. The experiment was conducted in the experimental area of the Animal Science Course, in the Institute of Agricultural Sciences and Technology / ICAT, which belongs to the Federal University of Mato Grosso - UFMT. It was used experimental silos with a capacity of 10 liters, with a Busen valve on its cover. It was determined dry matter, crude protein, ether extract, neutral detergent fiber, acid detergent fiber, hemicellulose, and total digestible nutrients. The gas production losses, the dry matter recovery and the effluents were calculated by weight difference. It was also measured the pH, buffering capacity and ammonia nitrogen. To evaluate the carbohydrate fractions, it were estimated carbohydrates fractions A + B1, B2 and C, protein fractions A, B1, B2, B3, C and the kinetic parameters of degradability fractions A, B, C, D, I and L. The variables dry matter, crude protein, neutral and acid detergent fiber and total digestible nutrients had increased linearly (P<0.05) with soybean hulls inclusion. Grass silages with soybean hulls showed higher dry matter recovery in relation to the control silage. pH values were also reduced (P <0.05). The regression equation of the total carbohydrates, fiber carbohydrate and the fractions B2 and C behaved quadratically. For nitrogen fractions B1 + B2, B3 and C, there were quadratic behavior, and fraction A presented an increasing linear behavior. The degradability parameters fractions A and B of dry matter increased linearly (P <0.05) with inclusion levels. It is concluded that the soybean hull inclusion level of 20% is sufficient to reduce the pH and to minimize gas losses and effluents, contributing to recovery nutrients. The inclusion of soybean hulls in the process of ensiling Brachiaria decumbens grass improves the proteins and carbohydrates fractions, reducing the silage non-degradable fractions.